PENERAPAN PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVMENT DIVISION) PADA MATERI MEKANIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA 1 MAN 15 JAKARTA - Irawati, Intan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Student Teams Achievment Division (STAD) is applied that students can work together and be responsible to their friends. The main idea of STAD is to motivate students in order to support and help each other to obtain the ability given by teachers. The application of STAD in the studies of physics is hoped that the motivation of students will increase so that the result of student‘s learning can be better. This action research consists of planning, action, observation, and reflection. The research was done from September until November 2010 in MAN 15 Jakarta. The subject is 242 students in the class of XI IPA 1. The data is obtained from the observation and descriptively analyzed. The increase of learning study is obtained after the action for two times. The obtained score above KKM is reached by 79% students after cycle 1 and 100% in cycle 2. The data analyst at PTK shows that the increasing learning of students in mechanics subject is successful by applying STAD. Keywords : learning, STAD, mechanics, studies result.